Regional Hydrological Response to Climate Change - Jones, J.A.; Changming Liu.; Ming-Ko Woo.; Hsiang-Te Kung.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1996)
This volume arises from the work of the International Geographical Union Working Group on Regional Hydrological Response to Climate Change and Global Warming under the chairmanship of Professor Changming Liu (1992-96). The book consists mostly of peer-reviewed papers delivered at the Working Group's first three scientific meetings held in Washington, D.C. (1992), Lhasa, Tibet (1993) and Moscow (1995). These have been supplemented by a few additional chapters that have been specifically commissioned in order to give a well-rounded coverage of the global and scientific aspects of the topic. As editors, we have sought to balance state-of-the-art reviews of methodology and regional research with detailed studies of specific countries and river basins. In the spirit of the IGU, we have devoted particular effort to encouraging contributions from scientists in the non-English-speaking world. These chapters provide valuable evidence of recent climatic change and predictions of future hydrological impacts from parts of the world where little detailed work has been conducted hitherto. They provide much valuable information that is new and interesting to an international audience and is otherwise very difficult or impossible to acquire. It is hoped that the present volume will be not only a record of current achievements, but also a stimulus to further hydrological research as the detail and spatial resolution of Global Climate Models improves. One notable aspect that emerges from a number of the contributions is that many, though by no means all, recent hydrological trends are in line with global warming predictions.
1. Predicting the Hydrological Effects of Climate Change -- Section I Sensitivity of the Global Hydrosphere Section Summary -- 2. An Introduction to Global Water Dynamics -- 3. Modelling the Biospheric Aspects of the Hydrological Cycle: Upscaling Processes and Downscaling Weather Data -- 4. Trends in Historical Steamflow Records -- Section II Regional Implications of Global Warming Section Summary -- 5. Hydrology of Northern North America under Global Warming -- 6. Current Evidence on the Likely Impact of Global Warming on Hydrological Regimes in Europe -- 7. The Impact of Climatic Warming on Hydrological Regimes in China: An Overview -- Section III Precipitation Change and Variability Section Summary -- 8. The Influence of Topography, Season and Circulation on Spatial Patterns of Daily Precipitation -- 9. Use of Artificial Neural Networks in Precipitation Forecasting -- 10. Generation of Sequences of Air Temperature and Precipitation for Estimation of the Hydrological Cycle in Changing Climatic Conditions in Poland -- 11. Some Aspects of Climatic Fluctuation at Four Stations on the Tibetan Plateau during the Last 40 Years -- 12. The Influences of the North Atlantic Oscillation, the El Niño/Southern Oscillation and the Quasi-Biennial Oscillation on Winter Precipitation in Ireland -- Section IV Impacts on Snow, Ice and Meltwaters Section Summary -- 13. Runoff Formation and Discharge Modelling of a Glacierized Basin in the Tianshan Mountains -- 14. Impact of Future Climate Change on Glacier Runoff and the Possibilities for Artificially Increasing Melt Water Runoff in the Aral Sea Basin -- 15. Glaciers and Snowcover in Central Asia as Indicators of Climate Change in the Earth-Ocean-Atmosphere System -- 16. Global Warming and the Trend toward Dryness in the Frigid High Mountains and Plateau of Western China -- Section V The Water Balance and Changing Regional Resources Section Summary -- 17. A Method to Assess the Effects of Climatic Warming on the Water Balance of Mountainous Regions -- 18. Sensitivity Analyses for the Impact of Global Warming on Water Resources in Wales -- 19. Potential Hydrological Responses to Climate Change in Australia -- 20. Dynamics of Stage Fluctuation in Yangzhouyongcuo Lake, Tibetan Plateau -- 21. Derivation of Surface Temperature, Albedo, and Radiative Fluxes over the Tibetan Plateau Based on Satellite Measurement -- 22. Climatic Warming and its Impact on the Water Resources of the Yalong River, China -- 23. The Probable Impact of Global Change on the Water Resources of Patagonia, Argentina -- 24. Long Term Trends in the Water Balance of Central Japan -- Conclusions -- 25. The Impact of Global Warming on Regional Hydrology and Future Research Priorities.
Keywords: Hydrogeology; Atmospheric sciences; Geography; Hydrogeology; Atmospheric Sciences; Geography, general